Dabartinės lietuvių kalbos priesagos -ėti denominatyviniai statyvai - Pakerys, Jurgis (Baltistica, 2006)
DENOMINATIVE STATIVES IN -ėti IN MODERN LITHUANIAN Denominative verbs in -ėti, -ėja are predominantly inchoative in Modern Lithuanian (senė́ti, -ė́ja ‘to become old’ : sẽnas ‘old’, akmenė́ti, -ė́ja ‘to harden, to turn into stone’ : akmuõ, -eñs ‘stone’). There is a relatively small group of synchronically or diachronically analyzable denominatives in -ėti which have stative meaning. I have tried to compile a preliminary list of these verbs from the electronic edition of Dabartinės lietuvių kalbos žodynas (Dictionary of Modern Lithuanian, 2003, DŽ5). The present stem of denominative statives in -ėti varies and can be one of the following four: (1) ja-stem in -ė-ja (gars-ė́-ti, gars-ė́-ja ‘is known, famous’ : garsùs ‘known, famous’), (2) i-stem (šykšt-ė́-ti, šỹkšt-i ‘is stingy’ : šykštùs ‘stingy’), (3) i-stem plus reflexive marker (bjaur-ė́-ti-s, bjaũr-i-si ‘be disgusted’ : bjaurùs ‘disgusting’), (4) a-stem (vert-ė́-ti, ver̃t-a ‘to be worth’ : ver̃ta ‘it is worth’). I have used a frequency dictionary (DDRKŽ, 1998) to separate rare and dialectal cases from the verbs of the main lexicon of Modern Lithuanian (henceforth “rare list” and „main list“). The main list of type 1 (-ėja) includes garsė́ti : garsùs ‘to be known, famous’ and malonė́ti ‘to be kind’ : malonùs ‘kind’. Rare or dialectal are badė́ti ‘to starve’ : bãdas ‘starvation’ (= Modern Lithuanian badáuti), dagė́ti ‘(figurative) to be prickly, biting’ : dagùs ‘prickly, biting’ (cf. also dagỹs ‘thistle’), ganė́ti ‘to be enough’ : ganà ‘enough’ (cf. OCS gonĕti, gonĕjetъ), gardė́ti ‘to be delicious, tasty’ : gardùs ‘delicious, tasty’, grožė́ti ‘to be nice, beautiful’ : gražùs ‘nice, beautiful’, grõžis ‘beauty’, padorė́tis ‘to dear, to consider appropriate (of clothing, behaviour)’ : padorùs ‘appropriate, decent’, skanė́ti ‘to be delicious, tasty’ : skanùs ‘delicious, tasty’. Type 2 (i-stem) posits some problems, because it is not always easy to prove the denominative origin of some verbs. The synchronic interpretation is usually obscured by the general tendency of Modern Lithuanian to derive deverbative u-stem adjectives from primary or secondary (the so called „mixed type“ which includes presents in -a, -ia, -i and -o beside suffixed infinitive stems) verbs. The main list of less problematic cases of type 2 includes gailė́ti, gaĩl-i ‘to feel sorry, pity’ : gaĩla ‘(impers.) it is a pity’, mylė́ti, mýl-i : dial., Old Lithuanian mýlas (cf. Latvian mĩlêt : mīls, mĩļš, Old Prussian milijt : mijls, Bulgarian милея, Macedonian милее beside common Slavic *milъ), šykštė́ti, šỹkšti-i ‘to be stingy’ : šykštùs ‘stingy’, viešė́ti, viė̃š-i ‘to be on a visit’ : (rare, archaic) viẽšis, -ỹs ‘guest’ (cf. Latvian viêsêt(ies)2 : vìesis). Problematic (at least from the synchronic point of view) cases can be exemplified by tylė́ti, tỹl-i and tingė́ti, tìng-i. The first one could be deverbative in origin if we accept the comparative evidence from Slavic (OCS tьlĕti ‘modern, vergehen’), Germanic (Gothic þulan, -aiþ ‘ertragen, dulden’) and Celtic (Old Irish -tuili ‘schläft’). The second one could be denominative if Lithuanian tingùs is considered archaic based on correspondences in Slavic (*tęgъkъ, cf. OCS otęgъčiti, -ati; note also prefixed inchoative *-ē- verb otęžati ‘to become burdened’) and Germanic (Old Icelandic þungr). The list of rare verbs includes non-problematic skonė́ti, skõn-i, skomė́ti, skõm-i ‘to be delicious, tasty’ (: skõnis, skõmas ‘taste’), a lengthened grade deverbative gorė́ti, gõr-i ‘to experience a bitter taste’ (beside garė́ti, gãr-i), an etymologically unclear spulė́ti, spùl-i (denominative derivation could be implied by the existence of gorùs, spulùs, but note the aforementioned general tendency to form deverbative adjectives in Modern Lithuanian) and skardė́ti, skar̃d-i ‘to echo, to sound’ (related to the family of kerd-/kird- verbs or simply denominative beside skardùs ‘sonorous’). Type 3 (i-stem plus reflexive marker) covers a group of verbs expressing a certain attitude or evaluation and can be paraphrased as ‘to consider something / someone (or a situation in general) to have the quality of the base adjective or noun’, cf.: jis šlỹkšt-i-si (inf. šlykštė́tis) tuo valgiu ‘he considers that dish disgusting’ (: šlykštùs ‘disgusting’). Type 3 is almost unproblematic, because the possibility of deverbative formation of adjectives is blocked semantically in most of the cases. There is no model of adjective formation in Lithuanian which could be paraphrased as ‘the one who / which is evaluated by the activity of the speaker described by the base verb’ (vs. productive model of ‘the one who / which verbs’, e. g. pavydŭs ‘the one who envies’ : pavydė́ti, pavýdi ‘envy’, but šlykštùs ≠ ‘the one which is disgusted at’). Lithuanian drovė́tis, drõv-i-si ‘to be shy’ also belongs to type 3 because of its morphology, but is probably to be analyzed as a deverbative formation with root vowel lengthening (cf. Latvian druvêtiês ‘erschrecken, sich fürchten’, drudêt ‘zittern’). Type 4 (a-stem) has only one verb in standard Modern Lithuanian: vertė́ti ‘(impers.) to be worth’ : ver̃ta ‘it is worth’. Some other verbs based on predicatively used neuter adjective forms or nouns could have probably belonged to this type (cf. ganė́ti, -ė́ja : ganà, gailė́ti, gaĩl-i : gaĩla), if their nominal ending was reinterpreted as a 3rd present indicative (cf. the deverbative type tekė́ti, tẽka), but was later substituted by stems in -i- and -ė-ja. My main conclusion is that denominative statives in -ėti are an unproductive derivational category in Modern Lithuanian. It is still possible to identify some isolated groups characterized by presents in -ė-ja, -i, -i-si or -a. Predominant inchoative semantics of Lithuanian denominatives in -ėti is probably to be considered an innovation. As inchoatives in -ėti, -ėja started to gain ground, at least some statives adopted i-stem presents (a typical feature of deverbative statives). If Indo-European formations in *-eh1- primarily had presents in *-eh1-i̯e/o- (as argued by Jasanoff 200212003, 147; cf. reconstructions of athematic inflection *-eh1-ti by Watkins 1971, 83; Jasanof f 1978, 124; Ruijgh 2004, 56 and zero-grade suffix in *-e-h1-ie/o- suggested by Rasmussen 1993, 481 and Hardarson 1998, 337), the more archaic morphology was taken over by the dominating inchoative type in Lithuanian, while the possibly archaic stative type lost the morphological uniformity of the present stem and drifted towards deverbative i-presents. Many of the latter ones became derivationally obscure as verbs in -ėti, -i can be considered as bases for the productive formation of deverbative u-stem adjectives in Modern Lithuanian. The space left by (formerly productive?) statives in -ėti was taken over by new denominative suffixes, cf.: gudr-áuti ‘to act using tricks’ : gudrùs ‘clever, cunning’, draug-áuti ‘to be friends’ : draũgas ‘friend’, balt-úoti ‘to be white’ : báltas ‘white’, šnip-inė́ti ‘to spy’: šnìpas ‘spy’.